2021
DOI: 10.5863/1551-6776-26.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Perspectives on Prescription Opioid Misuse and Medication Safety

Abstract: OBJECTIVES This study explored adolescents' perspectives on prescription opioids, opioid safety and misuse, and sources of opioid information. METHODS High school students participated in focus groups that elicited information about adolescent perspectives on prescription opioids and opioid safety. Demographic information was collected. Focus groups consisted of 5 to 8 student participants and 2 moderators. Focus groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…9,12 Literature has identified gaps in adolescent knowledge of proper opioid use and storage. 54 This lack of awareness in adolescents can be addressed by developing proper educational interventions that conform not only to…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Literature has identified gaps in adolescent knowledge of proper opioid use and storage. 54 This lack of awareness in adolescents can be addressed by developing proper educational interventions that conform not only to…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents that are prescribed opioids before the 12th grade have a 33% increase in the risk of future opioid misuse [ 4 ]. Therefore, adolescents represent a vulnerable population since they have limited knowledge about opioid medications and how opioid misuse is defined [ 5 , 6 , 7 , 8 ]. A family-driven intervention is essential given the known misuse behaviors that occur within households [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that adolescents have inadequate knowledge and understanding about opioid use and safety [12][13][14]. These studies suggest that adolescents are well-informed on how to use prescription opioids; however, they are underinformed of the addictive potential of opioids, the risks of overdose, and the availability of naloxone (Narcan, Emergent Operations Ireland) to reverse an opioid overdose [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that adolescents are well-informed on how to use prescription opioids; however, they are underinformed of the addictive potential of opioids, the risks of overdose, and the availability of naloxone (Narcan, Emergent Operations Ireland) to reverse an opioid overdose [15,16]. Additionally, many adolescents are not able to correctly identify which medications are opioids and which are not [13].…”
Section: Introductionmentioning
confidence: 99%